Low alanine transaminase is not associated with increased rate of mortality in patients with advanced lung cancer. Issue 1 (1st January 2017) - Dagan, Amir; Sella, Tal; Urban, Demian; Onn, Amir; Bar, Jair; Segal, Gad
Abstract: Background: Low alanine transaminase (ALT) has been shown to serve as a marker for sarcopenia and frailty in both healthy populations and in patients with chronic illness. Its yield in cancer patients in general and in particular in lung‐cancer patients was not assessed. Methods: Lung cancer patients presenting to an outpatient thoracic oncology clinic in a tertiary hospital were included. ALT plasma levels as well as other potential prognostic factors were collected retrospectively. Associations of those factors with survival were examined by univariate and multivariate analyses. Results: 203 patients were eligible for analysis, of which 149 (73.4%) were diagnosed to have advanced disease. During median follow‐up period of 15.4 months, 79 (38.9%) died. The mean ALT level of activity was 17.53±7.8 IU/L. The following parameters were found to be associated with increased risk of mortality: histologic type, male gender, advanced disease and low performance status upon diagnosis. Low ALT levels were not found to be associated with increased risk of mortality. Conclusion: Low ALT activity levels, associated with sarcopenia, frailty and shortened survival in other patients' populations might not be predictive for shortened survival in lung cancer patients.